Molecular evidence on the protective effect of ellagic acid on phosalone-induced senescence in rat embryonic fibroblast cells. (February 2017) - Baeeri, Maryam; Momtaz, Saeideh; Navaei-Nigjeh, Mona; Niaz, Kamal; Rahimifard, Mahban; Ghasemi-Niri, Seyedeh Farnaz; Sanadgol, Nima; Hodjat, Mahshid; Sharifzadeh, Mohammad; Abdollahi, Mohammad
Abstract: Salient evidence testifies the link between organophosphorus (OPs) exposure and the formation of free radical oxidants; and it is well accepted that free radicals are one of the basic concerns of senescence. To show the oxidative features of phosalone (PLN) as a key member of OPs, to induce senescence in rat embryonic fibroblast (REF) cells and to demonstrate the beneficial effects of the known antioxidant ellagic acid (EA) in diminishing the PLN-induced toxic effects, the levels of cell viability, oxidative stress markers, inflammatory cytokines, telomerase activity, and the expression of the genes related to senescence were investigated. Our results lend support to the hypothesis that PLN enhances the entire premature senescence parameters of REF cells. This accounts for the mechanistic approval of the role of OPs in induction of senescence in rat fibroblasts. Moreover, incorporation of EA diminished PLN toxicity mainly through suppression of p38 and p53 at gene and protein levels, and tempered the inflammation factors (TNF-α, IL-1β, IL-6 and NF-κB), which further affected cell division. Analysis of cell cycle showed that the percentage of G0/G1 arrest, in REF cells treated by EA was elevated as compared to control and PLN treated cells. Graphical abstract: Highlights: PLN enhanced the oxidative stress, inflammatory response, and disrupted cell division. EA dose-dependently deactivated PLN-induced senescence in REFs. EA depressed PLN toxicity through repression of P38 and P53 at the gene and protein levels. EA promoted expression of telomerase in REFs of PLN-induced senescence.